Influence of Strain and Stress Triaxiality on the Fracture Behavior of GB 35CrMo Steel during Hot Tensile Testing - Zheng Li; Yajun Zhou; Sanxing Wang (Advances in Materials Science and Engineering)
To better understand cavitation nucleation and crack initiation in 35CrMo steel during high-temperature tensile processing and the effect of stress triaxiality on its fracture behaviors, uniaxial and notch high-temperature tensile tests were performed. The microstructure, fracture morphology, fracture strain, and stress triaxiality of the tested 35CrMo steel were then characterized and discussed. The results showed that crack formation in 35CrMo steel included stages of nucleation, growth, and microcavity aggregation. Scanning electron microscopy and energy-dispersive X-ray spectroscopy demonstrated that crack formation was closely related to the presence of steel inclusions. High-temperature tensile testing of samples with different notch radii showed that the fracture strain of 35CrMo steel was decreased with increasing stress triaxiality, that is, increased stress levels corresponded to decreased material plasticity. In addition, the recrystallization degree was decreased with increased stress triaxiality, and the grain size growth was slowed. The failure of 35CrMo steel occurred via ductile fracture, and low stress triaxiality, and high temperature conditions induced large and deep dimples on the fracture surface.